The emerging roles of functional imaging in ovarian cancer with peritoneal carcinomatosis. Issue 7 (July 2018) - An, H.; Lee, E.Y.P.; Chiu, K.; Chang, C.
Abstract : This article reviews the emerging roles of functional imaging in the assessment of peritoneal carcinomatosis in ovarian cancer, focusing on the use of diffusion-weighted magnetic resonance imaging (DW-MRI) and 2-[ 18 F]-fluoro-2-deoxy-d- glucose positron-emission tomography combined with computed tomography (PET-CT), their advantages and shortcomings as well as the added-value over conventional imaging.